Differential effects of epidermal growth factor receptor inhibitors in a single patient with neuropathic pain. Issue 3 (26th March 2021) - Cameron, Marte Grønlie; Kersten, Christian
Abstract : Neuropathic pain (NP) represents an unmet medical need, where analgesic responses to different epidermal growth factor receptor inhibitors (EGFR-Is) have been described. The human EGFR family of receptors consists of four members (human epidermal growth factor receptor, HER 1–4), signalling via different homodimer and heterodimer combinations. A 52-year-old man was treated with the EGFR-I cetuximab in a trial of severe NP. Pain scores decreased dramatically after blinded cetuximab, but not after placebo. On pain recurrence after the trial, he was prescribed the oral EGFR-Is erlotinib, gefitinib, and lapatinib without relief. However, treatment with the pan-HER-inhibitor afatinib was effective. After 4 years on afatinib, pain control remains excellent with manageable side effects. This is the first reported observation of differential effects of EGFR-Is on NP in the same patient and the first report describing NP relief with afatinib. Further understanding of the underlying pathophysiology could lead to development of EGFR-Is specifically targeting NP.